Cluster size frequency distribution for the eleven species used in this study. - Hanne Zillmer (21782030) (2025)
The log(Cluster size) plotted against the log(NClusters). The clustering for all species reveals that there are many clusters that only contain few pockets and only few clusters with many pockets, and overall, a power-law degree distribution is observed. The largest clusters are found in SOYBN, MAIZE, MOUSE.